The Impact of Apartment Development on Community Social Economic Life: Case Study on Strenkali Community-in Asemrowo, Surabaya - Sukriyah Kustanti Moerad; Windiani Windiani; Umi Trisyanti; Niken Prasetyawati (IPTEK Journal of Proceedings Series, 2020)
The aims of Development for the welfare of the community, but often this development affects changes in environmental arrangements around the area which are outside the development goals. Environmental changes due to unplanned human activities have a negative impact on other social groups. Environmental impacts have the meaning of changes that can be natural or unnatural. This article aims to describe the impact of the construction of the Gunawangsa apartment, which is located around the Asemrowo River, Surabaya. This study uses a qualitative method with a case study approach. The informants in this study are people who live in the Asemrowo strenkali which is directly adjacent to the Gunawangsa Apartment Building, abaout 22 families. The results of the study found that the Gunawangsa apartment building which has been going on for 3 years has not felt the impact of significant changes in improving the family economy. The community still feels that socio-economic life is not much different from before development. The results of the research also found that the very high position of the building had hindered the catch of the television signal so that people had difficulty accessing the signal and could not comfortably enjoy television programs that were previously enjoyed well